2011
DOI: 10.3844/ajabssp.2011.33.44
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance and Biomass Accumulation of a <i>Khaya ivorensis</i> Plantation in three Soil Series of Ultisols

Abstract: Problem statement: There was no information about the relationship between growth parameters, such as diameter and height and tree component biomass of Khaya ivorensis plantations with different soil types. The objectives of this study were, first, to determine and compare the growth of K. ivorensis in three different (Padang Besar, Durian and Rengam) soil series of Ultisols and, second, to develop an allometric equation that estimates the biomass accumulation of the K. ivorensis plantation in three different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 23 publications
(20 reference statements)
0
16
0
1
Order By: Relevance
“…R. apiculata shows comparatively higher percentage of stem biomass (62.55%) compared to branch (31.89%) and leaf (5.57%). However, Heryati et al (2011) mentioned that the amount of the stem biomass is closely related to the production of trees obtained through photosynthesis which is generally stored in the trunk. Similarly, Hossain et al (2008) reported the same proportions of biomass stem>branch>leaf>reproductive components for B. parviflora in Kuala Selangor, Malaysia Table 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…R. apiculata shows comparatively higher percentage of stem biomass (62.55%) compared to branch (31.89%) and leaf (5.57%). However, Heryati et al (2011) mentioned that the amount of the stem biomass is closely related to the production of trees obtained through photosynthesis which is generally stored in the trunk. Similarly, Hossain et al (2008) reported the same proportions of biomass stem>branch>leaf>reproductive components for B. parviflora in Kuala Selangor, Malaysia Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Total dry weight of those plant parts (stem, branch and leaf) were estimated as dry/fresh weight ratios (Brown, 1997). Allometric relationships were examined using independent variable D or combination of quadratic of D and H. The relationship between independent variable and components biomass and stem volume was described by a power function, Yi = aD b or Yi = a (D 2 H) b , where a and b are regression constant, D is tree diameter (cm), H is total height (m) and Yi is the dry biomass (kg) of a tree component i.e., stem, branch and leaf (Heryati et al, 2011). To choose the most appropriate biomass prediction of R. apiculata, both methods for stand biomass prediction were compared.…”
Section: Study Sitementioning
confidence: 99%
“…Wood or non-wood products harvesting have created large tracts of degraded secondary forest. Nowadays, degraded forest lands are becoming predominant and important forest type in the tropical countries due to scarcity of natural forest (Heryati et al, 2011a;2011b). Forest plantation program in Malaysia mostly involves dipterocarp species and other fast growing exotic species.…”
Section: Introductionmentioning
confidence: 99%
“…The Munchong series soil is suitable for rubber plants and it has been classified as first class soil for rubber in term of soil-crop suitability (Malaysian Rubber Board, 2009). Different types of soil influences the growth performance of the crop (Heryati et al, 2010). Munchong series soil is silty clay loam to silty clay with yellowish brown to strong brown.…”
Section: Introductionmentioning
confidence: 99%